Non-active surgical implants - joint replacement implants - specifice requirements for knee-joint replacement implants (ISO 21536:2007, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Raj, Caroline; T, Mahadevan; Wong, Darren; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Yusof, Shahril; Manickam, Thirumal; Fazan, Fazilah; et al. (2010)
ISO 21536:2007 provides specific requirements for knee joint replacement implants. With regard to safety, this International Standard specifies requirements for intended performance, design attributes, materials, design evaluation, manufacture, sterilization, packaging, information supplied by the manufacturer and methods of test.